2014
DOI: 10.4236/ce.2014.54036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pranayama on Fine Moter Coordination Ability of Children with Intellectual Impairment

Abstract: Approximately 2.5% to 3% of the children are intellectually impaired who lack fine motor coordination abilities like eye-hand coordination, grip strength in fingers, etc. There is a need to improve their condition for better survival. Pranayama has been found to be very effective in the case of general children in the development of these abilities. But there is very little study on the application of pranayama practice for children with intellectual impairment. In the present five mild intellectually impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Singh S and Singh JP (2014) assessed the impact of pranayama sessions for 60 days in children with intellectual impairment on fine motor coordination. The children were able to perform the “inserting pegs task,” which indicates that pranayama improves the fine motor coordination like eye‐hand coordination and grip strength in fingers . Bhavanani et al (2012) conducted a study to assess the neurological benefits of yoga by recording the Reaction Time in mentally challenged subject's pre‐ and post‐Mukha Bhastrika—a bellows type of pranayama .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh S and Singh JP (2014) assessed the impact of pranayama sessions for 60 days in children with intellectual impairment on fine motor coordination. The children were able to perform the “inserting pegs task,” which indicates that pranayama improves the fine motor coordination like eye‐hand coordination and grip strength in fingers . Bhavanani et al (2012) conducted a study to assess the neurological benefits of yoga by recording the Reaction Time in mentally challenged subject's pre‐ and post‐Mukha Bhastrika—a bellows type of pranayama .…”
Section: Discussionmentioning
confidence: 99%
“…The children were able to perform the "inserting pegs task," which indicates that pranayama improves the fine motor coordination like eye-hand coordination and grip strength in fingers. 16 Bhavanani et al (2012) conducted a study to assess the neurological benefits of yoga by recording the Reaction Time in mentally challenged subject's pre-and post-Mukha Bhastrika-a bellows type of pranayama. 17 Recent study by Ramanathan et al (2019) also reported a reduced reaction time in children with ASD following yoga training.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout, the thoracic muscles should be kept contracted. (8) Subject has to practice it as a 5-10 minute sessions, at least twice a day. If this is found unpleasant, one can try mini-sessions, palming for a period of 15 breaths, up to 20 times a day.…”
Section: Palming and Visualization With Kapalbhatimentioning
confidence: 99%
“…Pranayama "prana" + "yama" is the fourth limb of yoga which balances nervous system and improves mental clarity and physical coordination. (8) Yoga training enhances the grip strength, dexterity, confidence, self-efficiency, mental health, creativity, concentration, memory & intellectual abilities. Yoga also influence several motor functions including static motor performance, tweezer dexterity as well as visuomotor speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation